1999
DOI: 10.1021/bc990049y
|View full text |Cite
|
Sign up to set email alerts
|

RP463:  A Stabilized Technetium-99m Complex of a Hydrazino Nicotinamide Derivatized Chemotactic Peptide for Infection Imaging

Abstract: A HYNIC-conjugated chemotactic peptide (fMLFK-HYNIC) was labeled with (99m)Tc using tricine and TPPTS as coligands. The combination of fMLFK-HYNIC, tricine, and TPPTS with (99m)Tc produced a ternary ligand complex [(99m)Tc(fMLFK-HYNIC)(tricine)(TPPTS)] (RP463). RP463 was synthesized either in two steps, in which the binary ligand complex [(99m)Tc(fMLFK-HYNIC)(tricine)(2)] (RP469) was formed first and then reacted with TPPTS, or in one step by direct reduction of [(99m)Tc]pertechnetate with stannous chloride in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 14 publications
1
58
0
1
Order By: Relevance
“…Different biodistributions were observed for binary ligand 99m Tc complexes [ 99m Tc(XV120)(L) 2 ] [ Fig. 1: L is GH, mannitol, and glucamine and XV120 is cyclo(D-Val-NMeArg-Gly-Asp-Mamb(5-(6-(6-hydrazinonicotinamido)hexanamide)))].Animal studies have shown evidence of binding of the 99m Tc-labeled fMLFK-HYNIC to leukocytes in vivo and localization at the infection site [9][10][11][12][13][14][15][16][17][18]35]. 6-Hydrazinonicotinamide Derivatives as Bifunctional Coupling Agents 119 Liu et al [41] reported the 99m Tc-labeling of an HYNIC-derivatized platelet GPIIb/IIIa receptor antagonist (Scheme 1) using tricine as the coligand.…”
Section: Binary Ligand Technetium Complexesmentioning
confidence: 99%
See 3 more Smart Citations
“…Different biodistributions were observed for binary ligand 99m Tc complexes [ 99m Tc(XV120)(L) 2 ] [ Fig. 1: L is GH, mannitol, and glucamine and XV120 is cyclo(D-Val-NMeArg-Gly-Asp-Mamb(5-(6-(6-hydrazinonicotinamido)hexanamide)))].Animal studies have shown evidence of binding of the 99m Tc-labeled fMLFK-HYNIC to leukocytes in vivo and localization at the infection site [9][10][11][12][13][14][15][16][17][18]35]. 6-Hydrazinonicotinamide Derivatives as Bifunctional Coupling Agents 119 Liu et al [41] reported the 99m Tc-labeling of an HYNIC-derivatized platelet GPIIb/IIIa receptor antagonist (Scheme 1) using tricine as the coligand.…”
Section: Binary Ligand Technetium Complexesmentioning
confidence: 99%
“…Since then, the HYNIC technology has successfully been used for the 99m Tc-labeling of antibodies [3][4][5][6][7][8] and small biomolecules (BMs), including chemotactic peptides [9][10][11][12][13][14][15][16][17][18], somatostatin analogs [19][20][21][22][23][24][25],"stealth" liposomes [26,27], antisense oligonucleotides [28][29][30][31], a folate receptor ligand [32], and polypeptides [32][33][34]. A ternary ligand system (HYNIC, tricine, and trisodium triphenylphosphine-3,3¢,3≤-trisulfonate, TPPTS) has been used for the 99m Tc-labeling of chemotactic peptides [35] and leukotriene B 4 (LTB 4 ) receptor antagonists [36][37][38][39] for imaging infection and inflammation, integrin a v b 3 receptor antagonists for tumor imaging [40], and a glycoprotein IIb/IIIa (GPIIb/IIIa) receptor antagonist for imaging thrombosis [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the last decade, we have been using ternary ligand systems (HYNIC, tricine, water soluble phosphine or pyridine analog) for 99m Tc-labeling of small biomolecules, including chemotactic peptides [40] and LTB 4 antagonists [41,42] for imaging infection/inflammation, integrin α v β 3 antagonists for tumor imaging [27][28][29][30], and a GPIIb/IIIa antagonist for imaging thrombosis [43][44][45][46]. Regardless of the biomolecule, the Tc:HYNIC:L:tricine ratio in [ 99m Tc(HYNIC-biomolecule)(tricine)(L)] always remains 1:1:1:1 as demonstrated via mixed ligand experiments at the tracer level [43,44], and has been further confirmed by the LC-MS data of [ 99m Tc(HYNIC-biomolecule)(tricine)(L)] (L = TPPTS and ISONIC) at both macroscopic and tracer levels [47,48].…”
Section: Radiochemistrymentioning
confidence: 99%